2008
DOI: 10.1021/jp075873v
|View full text |Cite
|
Sign up to set email alerts
|

Quadruplex Structure of Polyriboinosinic Acid:  Dependence on Alkali Metal Ion Concentration, pH and Temperature

Abstract: The vibrational infrared (IR) absorption and vibrational circular dichroism (VCD) spectral changes of polyinosinic acid (polyI) as a function of alkali metal ion concentration, temperature and pH have been investigated to establish how changes in spectral features relate to the structural modifications of polyI. A single positive VCD couplet associated with the carbonyl absorption band is considered to be the signature of quadruplex structure for polyI. The disruption of the quadruplex structure with temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…3 On the other hand, previous work by Gansler et al (37) demonstrated the importance of secondary structure on the procoagulant ability of nucleic acids, finding that hairpin-forming RNA oligomers are not only more resistant to degradation but are also more procoagulant, and in particular, structure-forming RNA aptamers were shown to mediate PPK autoactivation. PolyG and polyI are known to form stable, non-canonical base-pairing structures such as G-quadruplexes (38,39). We previously reported that polyG RNA has substantial procoagulant activity (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…3 On the other hand, previous work by Gansler et al (37) demonstrated the importance of secondary structure on the procoagulant ability of nucleic acids, finding that hairpin-forming RNA oligomers are not only more resistant to degradation but are also more procoagulant, and in particular, structure-forming RNA aptamers were shown to mediate PPK autoactivation. PolyG and polyI are known to form stable, non-canonical base-pairing structures such as G-quadruplexes (38,39). We previously reported that polyG RNA has substantial procoagulant activity (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The other structure, 2KKA, was excluded because the reported structure contained a non-canonical inosine substituted for a guanine. Inosine disrupts G-quadruplex formation [70] and is used reduce the number of possible folding topologies for a polymorphic G-quadruplex sequence. Instead of using this structure to build our global fit model, we selected it to study how base substitution affects the structure in solution.…”
Section: Hydrodynamic Bead Modeling Of G-quadruplex Structuresmentioning
confidence: 99%
“…40,42 Infrared absorption and VCD changes correlate with structural changes of both polymers. The computations reported here were performed in a rough manner and provide preliminary results.…”
Section: G-rich Sequential Oligonucleotidesmentioning
confidence: 98%
“…VCD was also used for the investigation of quadruplex structures formed in the homopolynucleic acids polyriboguanylic (polyG) and polyriboinosinic acid (polyI). 40,42 Infrared absorption and VCD changes correlate with structural changes of both polymers. The computations reported here were performed in a rough manner and provide preliminary results.…”
Section: G-rich Sequential Oligonucleotidesmentioning
confidence: 98%